2012
DOI: 10.1101/lm.027581.112
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of contextual fear memory formation, specificity, and persistence in mice

Abstract: Pinpointing the precise age when young animals begin to form memories of aversive events is valuable for understanding the onset of anxiety and mood disorders and for detecting early cognitive impairment in models of childhood-onset disorders. Although these disorders are most commonly modeled in mice, we know little regarding the development of learning and memory in this species because most previous studies have been restricted to rats. Therefore, in the present study, we constructed an ontogenetic timeline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
77
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 73 publications
10
77
1
Order By: Relevance
“…The apparently off-task behavior may be analogous to off-task behavior in the SDR procedure inferred from adolescent omission errors. The differences seen with IRA contrast with studies reporting moderate or no differences between adolescents and adults on fear conditioning, water-maze performance, or acquisition of responding under variable interval schedules of reinforcement (Akers, et al, 2012; Broadwater & Spear, 2013; Kendig, et al, 2013). …”
Section: Discussioncontrasting
confidence: 75%
“…The apparently off-task behavior may be analogous to off-task behavior in the SDR procedure inferred from adolescent omission errors. The differences seen with IRA contrast with studies reporting moderate or no differences between adolescents and adults on fear conditioning, water-maze performance, or acquisition of responding under variable interval schedules of reinforcement (Akers, et al, 2012; Broadwater & Spear, 2013; Kendig, et al, 2013). …”
Section: Discussioncontrasting
confidence: 75%
“…Our group has observed elevated activity in the HPC during extinction retrieval in the juvenile mice, which suggested that HPC is likely to be functioning at this age [32]. This context-independent in cued fear memory extinction retrieval in the juvenile is consistent with previous findings [16,[33][34][35]. We also found that the output portion of the circuitry mediating extinction retrieval (IL to BLA) to be functional while the inputs portion (HPC to PFC) is not.…”
Section: Fear Extinction During Developmentsupporting
confidence: 80%
“…Infantile amnesia was initially described in humans and refers to the inability to recall experiences that occurred over the first 3 -5 yr of life (for review, see Campbell and Spear 1972). Extensive systematic studies of infantile amnesia using nonhuman animals (typically mice or rats) in a variety of aversive learning paradigms have shown that younger animals forget faster than older animals (Campbell and Campbell 1962;Campbell 1967;Campbell et al 1968;Feigley and Spear 1970;Schulenburg et al 1971;Anderson and Riccio 2005;Akers et al 2012Akers et al , 2014Kim et al 2012). Consistent with the present findings, long-term retention deficits in young animals are shown even when immediate, or short-term retention is equivalent across ages, thus confirming that long-term retention deficits do not simply reflect poorer initial learning.…”
Section: Discussionmentioning
confidence: 99%